A review of the role of Haemophilus influenzae in community-acquired pneumonia. Issue 1 (December 2015) - Slack, Mary
Abstract In an era whenHaemophilus influenzae type b (Hib) conjugate vaccine is widely used, the incidence of Hib as a cause of community-acquired pneumonia (CAP) has dramatcally declined. Non-typeableH. influenzae (NTHi) strains and, occasionally, other encapsulated serotypes ofH. influenzae are now the cause of the majority of invasiveH. influenzae infectons, including bacteraemic CAP. NTHi have long been recognised as an important cause of lower respiratory tract infecton, including pneumonia, in adults, especially those with underlying diseases. The role of NTHi as a cause of non-bacteraemic CAP in children is less clear. In this review the evidence for the role of NTHi and capsulated strains ofH. influenzae will be examined.